Qualitative evaluation of total mixed ration silage containing forage cactus and guinea grass as a nutritional alternative for feedlot-finished sheep - dos S. Sá, Wilma Cristina C.; Santos, Edson M.; de Oliveira, Juliana S.; de Araújo, Gherman G. L.; Perazzo, Alexandre F.; Pereira, Danillo M.; Santos, Francisco Naysson de S.; Macêdo, Alberto Jefferson da S.; Cruz, Gabriel F. de L.; Corrêa, Yohana R.; Pereira, Gildenia A.; Cesar Neto, José M. [UNESP]; et al. (Wiley, 2025)
This study aimed to evaluate the fermentation characteristics, microbial populations, losses, aerobic stability and chemical composition of total mixed ration based on forage cactus and different ratios of Guinea grass at four storage times (7, 15, 60 and 100 days). Five diets were formulated with forage cactus as the main ingredient, with varying Guinea grass inclusion ratios: 0, 10, 20, 25 and 30% on a dry matter basis. The experimental design used was a completely randomised design with a factorial arrangement and three replicates. The silages had pH values of approximately 4.0. Lactic acid bacteria were predominant in all silages, and this predominance increased after 7 days of ensiling in all diets, ranging from 8.0–10.1 log10 cfu g−1 of silage. Silages with 10% and 20% guinea grass showed aerobic deterioration, while the others remained stable throughout the aerobic stability test. Guinea grass in combination with forage cactus can be added in total mixed ration silages up to a level of 30%, without compromising the chemical composition, silage losses or fermentative profile. However, considering aerobic stability, the addition of 10% and 20% guinea grass resulted in greater deterioration after 48 h of exposure to air.
Keywords: Ensiling; fermentation profile; Megathyrsus maximus; Nopalea cochenillifera; organic acids